The long game - Armas, Elena; OverDrive, Inc. (New York, NY : Atria Paperback, an Imprint of Simon & Schuster, Inc, 2023)
"A disgraced soccer executive reluctantly enlists the help of a retired soccer star in coaching a children's team"--
Electronic book.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Novels; Electronic books